Gamma 60Co Ray Irradiation on the Diversity of Two Varieties of Onion Red (Allium ascalonicum L) TSS (True Shallot Seed) - Ida Retno Moeljani; Hadi Suhardjono; Djarwatiningsih (Future Science)
TSS (True Shallot Seed) as a solution to the problem of seed availability, but farmers still use tuber seeds for shallot production. This is because the aspects of TSS shallot cultivation are still not widely known and must be reviewed. This study aims to obtain information on the variability of onion varieties from TSS seeds compared with those from tubers. This research was conducted on farmers' land in Ketindan village, Lawang district, Malang Regency. The research was carried out using a randomized block design with two factors, namely: The first factor consisted of two treatments: T1: TSS came from the Bauji variety and T2: TSS came from NTB Ketamonca and the second factor was the radiation dose with three treatments R1: gamma ray radiation dose 60Co 15 Gy, R2: 60Co gamma ray radiation dose 30 Gy, R3: 60Co gamma beam radiation side with three repetitions. Bauji (tuber seed) control variety. The results of this study were that there were variations in the character of the color and shape of the tubers in the two varieties of red onion TSS. Bauji variety has higher leaf length, pseudo stem diameter, leaf diameter and number of leaves per pseudo stem compared to comparison varieties (Bauji, seed from tuber). Based on the dry weight value per clump on the average variety, the Bauji BM 8705 variety was not significantly different from the comparison varieties (Bauji, seed from tubers).